Purification and Characterization of Extracellular Lipase from Staphylococcus epidermidis (MTCC 10656) - Sirisha Edupuganti, Lakshmi Parcha, Lakshmi Narasu Mangamoori (Journal of Applied Pharmaceutical Science, 2017)
Lipases are hydrolytic enzymes with wide range of industrial applications. In the present study Staphylococcus epidermidis strain L2 with ability to produce extracellular lipase enzyme has been isolated from cloth samples collected from the diary industry. The extracellular lipase enzyme has been purified to homogeneity. The purified enzyme has shown a specific activity of 123.95U/mg. The molecular weight of the purified lipase enzyme was found to be 28KDa. The pH and temperature optima of the enzyme were recorded as 7.5 and 40°C respectively. The lipase enzyme has shown stability and activity in presence of varying concentrations of emulsifier and different substrates.
Keywords: Extracellular lipase, Staphylococcus, purification.